Effect of cobalt content on nonisothermal crystallization kinetics of Febased amorphous alloys (2020)
ABSTRACT : In the present study, FeSiBP and FeCoSiBP ribbons with a fully amorphous structure were made by melt spinning technique. A detailed analysis of the isochronal crystallization behavior is presented in this paper. The influence of cobalt on the crystallization kinetics of the alloys was studied under isochronal conditions using differential scanning calorimetry (DSC). Apparent and local activation energy values were determined by Kissinger, Ozawa and Kissinger-Akahira-Sunose (KAS) methods. The results indicate that appropriate amounts of cobalt can significantly enhance the thermal stability of Fe-based alloys, through an increase in nucleation activation energy from 538kJ/mol to 701kJ/mol, obtained by Kissinger method. Furthermore, with the method proposed by Matusita, it was possible to obtain global values for the Avrami exponent, noting that from a general perspective, Co changes the mechanism from diffusion controlled to interface controlled. This leads to the conclusion that the crystallization process is complex and takes place in more than one stage. Therefore, the determination of nucleation mechanisms and dimensional growth is difficult due to the inapplicability of the Johnson-Melh-Avrami (JMA) model. As such, a study under isothermal conditions is suggested, in order to achieve a full understanding of the mechanisms involved.